IDENTIFIKASI CENDAWAN TERBAWA BENIH PADI MENGGUNAKAN BLOTTER TEST DAN PREPARASI METODE SELOTIP - Effi Alfiani Sidik (Universitas Tidar, 2021)
Seed health testing can help to limit the danger of seed-borne diseases, particularly fungus, spreading from one location to another. To detect several types of seed-borne fungus, seed testing utilizing the filter paper incubation method (blotter test) was carried out. Under a microscope, the isolates acquired after incubation were identified. The creation of sample preparations becomes a crucial key in facilitating the easy and practical identification of fungus. The purpose of this study was to use a blotter test to identify rice seed-borne fungus using the tape method to prepare sample. Incubation was accomplished by planting the seeds on Whatman paper and exposing them to 12 hours of light and 12 hours of darkness alternately. The tape method was used for the preparation of the fungus that grows on the seeds. The tape method is a quick, simple, and practical way to detect the fungus that covers the seed's surface. Tilletia barclayana, Phoma sp., Fusarium sp., Aspergillus niger, Desclera oryzae, Curvularia lunata, C. pallescens, Stemphylium sp. and Nigrospora sp. have all been detected.Keywords: Benih padi, Mikroskop, Morfologi cendawan, Patogen tular benih, Seed-borne